2014
DOI: 10.1016/j.ijlp.2014.02.006
|View full text |Cite
|
Sign up to set email alerts
|

The influence of neighborhood characteristics on police officers' encounters with persons suspected to have a serious mental illness

Abstract: Objective Police officers’ decisions and behaviors are impacted by the neighborhood context in which police encounters occur. For example, officers may use greater force and be more likely to make arrests in disadvantaged neighborhoods. We examined whether neighborhood characteristics influence police encounters with individuals suspected to have a serious mental illness, addictive disorder, or developmental disability. Method We obtained data on 916 encounters from 166 officers in six jurisdictions in Georg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 18 publications
1
8
0
Order By: Relevance
“…Previous studies demonstrate that police-community relations are more tenuous in neighborhoods with greater proportions of racial minorities and high levels of social disadvantage (Krishan et al 2014;La Vigne et al 2017;Weitzer et al 2008). For this reason, it is likely that police departments in communities with a larger proportion of racial minority residents or a higher level of social disadvantage may feel pressure to implement BWCs to improve their relationship with the community.…”
Section: Characteristics Of Environmentmentioning
confidence: 99%
“…Previous studies demonstrate that police-community relations are more tenuous in neighborhoods with greater proportions of racial minorities and high levels of social disadvantage (Krishan et al 2014;La Vigne et al 2017;Weitzer et al 2008). For this reason, it is likely that police departments in communities with a larger proportion of racial minority residents or a higher level of social disadvantage may feel pressure to implement BWCs to improve their relationship with the community.…”
Section: Characteristics Of Environmentmentioning
confidence: 99%
“…Set 1 included unemployment rate, median income, percentage of families below the federal poverty level, percentage of high school graduates, percentage receiving public assistance, and percentage of female-headed households for each zip code. These characteristics were included together because they have typically been used in previous neighborhood disadvantage research (29,30). The Kaiser-Meyer-Olkin measure of sampling adequacy was adequate (28).…”
Section: Analysesmentioning
confidence: 99%
“…In order to achieve a representative sample of the city, five police departments located in the center and in the western, eastern, southern, and northern districts were chosen. Pervious research showed that police interactions with individuals with mental illnesses are not equally allocated in neighborhoods (Krishan et al, 2014). Therefore, we deemed this approach necessary as different police departments were located in neighborhoods with potentially differing frequencies in police request involving mental disorders.…”
Section: Methodsmentioning
confidence: 99%